Immunomodulatory effects of exercise in cancer prevention and adjuvant therapy: a narrative review - Lyu, Da-wei (Frontiers in Physiology, 2024)
Successful application of cancer immunotherapy has rekindled renewed hope in cancer patients. However, a number of patients are unresponsive to immunotherapy and related treatments. This unresponsiveness in cancer patients toward different treatment regimens can be mainly attributed to the severe immune dysfunction in such patients. Several reports indicate that physical exercise can significantly lead to improved cancer patient outcomes. Since exercise gets immense response from the immune system, it can be utilized in improving the immune function. The leukocytes with enhanced function are substantially mobilized into the circulation by a single bout of intense physical exercise. Long-term, chronic physical exercise results in greater muscle endurance and strength, and cardiorespiratory function. This exercise regime is also useful in improving T cell abundance and reducing dysfunctional T cells. The current available data strongly justifies for future clinical trials to investigate physical exercise use as an adjuvant in cancer therapy, however the optimal parameters using exercise for a defined outcome is yet to be established. The components of immune system associate with almost every tumorigenesis step. The inter-relationship between inflammation, cancer and innate immunity is recently getting acceptance; however, the underlying cellular and molecular mechanisms behind this relationship is yet to be solved. Several different studies suggest for physical exercise-mediated induction of immune cells to elicit antitumorigenic effects. This indicates for the potential of exercise in modulating the behaviour of immune cells to inhibit tumour progression. However, further mechanistic details behind physical exercise-driven immunomodulation and anti-cancer effects need to be determined. This review aims to summarize and discuss the association between physical exercise and immune function modulation and the potential of exercise as an adjuvant therapy in cancer prevention and treatment.